SENSORY, ORGANOLEPTIC, NUTRITIONAL QUALITY AND YIELD OF SWEET CORN (ZEA MAYS SACCHARATA STURT.) AS INFLUENCED BY AGRONOMIC MANIPULATIONS - GAURAV MAHAJAN, (The Bioscan, 2015)
A set of treatments involving different levels of sulphur, fertility and plant population and its effect on the sensory (aroma), organoleptic quality, nutrient uptake and yield of sweet corn were evaluated for field studies during the consecutive summer seasons from of 2008 to 2010 at Institute of Agricultural Sciences, Banaras Hindu University. The results revealed that highest levels of sulphur, fertility and plant population had a marked influence on kernel DMS, MMS and MET content. The crop when supplied with F3 (160-34.4-49.8 kg NPK/ha), it elucidate significant effect on uptake of nutrients by kernels coupled with better organoleptic quality coupled in an average increase of 26% in the kernal yield. Whereas, wider spacing as result of 50,000 plants ha-1 outperformed all the characters under observation except yield. From the study, it is concluded that for obtaining better sensory, organoleptic, nutritional quality in sweet corn, the crop of sweet corn should be grown with the fertility level of 160-34.4-49.8 kg NPK/ha maintaining a plant population of 50,000 plants/ha and application of 40 kg/ha sulphur.